2010
DOI: 10.1021/la904623e
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Micellar Films of Amphiphilic Block Copolymer Micelles: Control on Micelle Opening and Closing

Abstract: We reported the deliberate control on the micelle opening and closing of amphiphilic polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) micellar films by exposing them to selective solvents. We first treated the micellar films with polar solvents including ethanol and water (pH = 4, 8, and 12) that have different affinities to P2VP. We observed opening of the micelles in all the cases. Both the size of opened pores and the opening rate are dependent on the solvency of different solvents for P2VP. We then expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 31 publications
3
70
0
Order By: Relevance
“…2011, 23,[2134][2135][2136][2137][2138][2139][2140][2141][2142][2143][2144][2145][2146][2147][2148] demonstrated that an increase in the pH value of the water in which BCP fi lms were incubated led to faster pore forming and larger pore sizes, while it exerted a completely opposite effect in the case of PS-b -P2VP. [ 40 ] …”
Section: Progress Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…2011, 23,[2134][2135][2136][2137][2138][2139][2140][2141][2142][2143][2144][2145][2146][2147][2148] demonstrated that an increase in the pH value of the water in which BCP fi lms were incubated led to faster pore forming and larger pore sizes, while it exerted a completely opposite effect in the case of PS-b -P2VP. [ 40 ] …”
Section: Progress Reportmentioning
confidence: 99%
“…The pore formation can be terminated simply by withdrawing the fi lms from the solvent, thus freezing intermediate opening pore morphologies with various pore sizes and surface topographies. Figure 2 shows four intermediate porous morphologies obtained by incubating PS-b -P2VP micellar fi lms in water (pH = 8) for different periods of time ranging from 30 s to 18 h. [ 40 ] In addition, it was found that in the same BCP system the pore openness of the BCP fi lm treated in water (pH = 8) for 18 h was similar to that of the BCP fi lm treated in ethanol for only 30 s, mainly because ethanol has a stronger interaction to P2VP chains than water (pH = 8), while the difference between the affi nity of ethanol and water to PS chains into which the swelling solvents penetrate plays a minor role. Since the micelle cores forming blocks are often weak polyelectrolytes, for instance, P2VP, P4VP, and PAA, some solution properties, such as pH values and ionic strength, greatly infl uence the kinetics of the pore-forming process, facilitating more controls in fi nely tuning the sizes and morphologies of the resultant pores.…”
Section: Morphology Tuning Of the Poresmentioning
confidence: 99%
See 3 more Smart Citations